OCB-E among Chinese employees of different contract types. Issue 3 (24th March 2020) - Ren, Shuang; Tang, Guiyao; Kim, Andrea
Abstract : Purpose: Drawing on a motivational model of proactive behavior, this study theorizes that employment status, reflective moral attentiveness (RMA), and organization-based self-esteem (OBSE) constitute the can-do, reason-to, and energized-to motivational states, which interact to induce organizational citizenship behavior toward the environment (OCB-E). Design/methodology/approach: The authors conducted random coefficient modeling (RCM) analysis with a multisource, time-lagged data set collected from 235 employees in Chinese firms. Findings: This RCM analysis found that more OCB-E resulted from standard employees with higher levels of RMA and OBSE. Originality/value: The value of this research lies in understanding of the antecedents of green behavior at the individual level by identifying specific motivational states and highlighting the coexistence of motivational states in predicting OCB-E. These findings provide new insight into the theory of developing and managing green OCB performers in today's workplace characterized by workforce mixing.